Association between social media addiction and sleep quality among undergraduate nursing students: a cross-sectional study - Setyowati Lilis; Kurnia Anggraini Dwi; Lestari Windi; Karuncharernpanit Sirikul (Sciendo, 2023)
To examine the association between social media addiction and sleep quality among undergraduate nursing students.